A novel method for fabrication of high-flux zeolite membranes on supports with arbitrary geometry. Issue 17 (4th April 2019) - Yu, Liang; Holmgren, Allan; Hedlund, Jonas
Abstract : A new widely applicable masking method, relying on rendering the support hydrophobic and thereby protected from the synthesis mixture, was developed for the preparation of zeolite membranes on supports with arbitrary geometries. Abstract : A novel procedure for the preparation of high-flux zeolite membranes was developed. This method relies on rendering the support hydrophobic, and thereby protected from the synthesis mixture and invasion of the support pores, while the cationic polymer on the surface still allowed deposition of zeolite seeds. Both high-flux MFI and CHA zeolite films were grown on both discs and tubular supports, which illustrates the applicability of the method to arbitrary membrane geometries. Typically, MFI disc membranes showed a very high CO2 permeance of 85 × 10 −7 mol m −2 s −1 Pa −1 and a CO2 /H2 separation selectivity of 56 at 278 K and CHA disc membranes showed a very high CO2 permeance of 79 × 10 −7 mol m −2 s −1 Pa −1 and a CO2 /CH4 separation selectivity of 76 at 249 K. As the method is applicable to supports with complex geometries, it is suitable for preparation of membranes for industrial applications.